[The issue of good governance and socio-political realities in Africa] : [the case of Ivory Coast] - (:unkn) unknown (My University, 2013)
After a semantic analysis of the notion of Good Governance, to light the sense of this complex notion, notion the origins of which go back up to a rather distant time. This principle, which built itself through centuries, concerned at first the world of companies, before invading the field of the politics, in the quest of the best management of the public affairs, to satisfy at best the affairs of the State. As therapy, organized by the international institutions, to bring out the African states, often corrupted States, of the tunnel of the poverty and the underdevelopment, it showed itself ineffective. The good governance in its implementation, in Africa and in Ivory Coast, faces a world where the political game set, is influenced by clan, family, tribal links, which put the interest of the groups above the general interest, engendering a decay of the State, with an absence of ethics, responsibility of brightness in the decision-making, in the societies where the quest of the democracy is marked with the seal of the demagoguery, with a premium granted to the opacity in the management of the public affairs. This quest of efficiency is counterbalanced by the weight of the traditions and the practices inherent to the world of the Third World, the things which return the with difficulty effective management of the public affairs. However, the political arena does not escape the influence of the outside world, which influences decision-making, with public actors often subjected to the orders of this capitalist world, in a world marked with the seal of the globalization and with the globalization.
Keywords: African Research